Siła nowoczesnych narzędzi internetowych i ich wkład w rozwój e-biznesu - Jacek, Piotr (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
Article talks about the main issues of the topic, e-business and internet tools. In this paper I focus first on the issue of e-business, which is the basis thesis topic. It is in e-business best online tools help us, whose influence on the development of e-business wanted to present. In the next part I will try to present a possible Internet tools that can be used in e-business. It will be obviously the most important part, a vast compendium of the world of online possibilities. At the end you will be able to read the results of scientific studies that show how it is with the e-business among students of the University of Lodz and what they think about the role in this of all online tools. I think that after reading the article certainly agree with this thesis. At the end I will try to present my conclusions and a summary of the whole subject.